Exploration of student perception regarding the implementation of scripts to promote socially shared regulation of learning.: (Revista Electrónica Calidad en la Educación Superior, 2023)
Considering that some university program self-assessment processes incorporate the development of teamwork skills (TWS) as a criterion, it becomes essential to gauge students' perceptions regarding pedagogical efforts aimed at nurturing this capability. This study posits that TWS can be cultivated through learning activities fostering socially shared regulation of learning (SSRL) and socially shared metacognitive regulation (SSMR) processes within the university milieu. Building upon this premise, MSC-based scripts were introduced to promote SSRL, and the perceptions of university students regarding their implementation were explored. The findings indicate a significantly positive assessment of the utility of scaffolding methods in advancing SSRL, emphasizing the potential of such strategies in enhancing teamwork skills within higher education.
Keywords: Self-assessment; higher education; collaborative scripts; socially shared regulation of learning; student perceptions; socially shared metacognition